Marginalization and Revitalization of Tumula Offerings in Gorontalo Traditional Marriage: A Maqāṣid al-Sharīʿah and Islamic Ecotheological Perspective - Abdur Rahman Adi Saputera; Rivai Arifin; Rustan Rustan (Program Pascasarjana IAIN Langsa, 2026)
Previous studies on the traditional marriage of the Gorontalo community have primarily focused on ceremonial procedures, the relationship between adat (customary law) and Islamic law, and the cultural values embedded in marriage traditions. However, research specifically examining the marginalization of the Tumula offering as an ecological symbol in the Dutu ritual through an integrated Maqāṣid al-Sharīʿah and Islamic ecotheology perspective, while proposing an implementable cultural revitalization model, remains scarce. This research gap provides the foundation for the present study, which aims to analyze the factors contributing to the marginalization of Tumula; examine its relevance from the perspectives of Maqāṣid al-Sharīʿah and Islamic ecotheology; and formulate a cultural revitalization model that responds to contemporary social transformation. This study employed a qualitative field research approach conducted in East Kota District, Gorontalo City. Data were collected through observations; in-depth interviews with customary leaders, religious scholars, and community members; as well as documentation; and were analyzed using an interactive qualitative analysis model. The findings indicate that the marginalization of Tumula is driven by modernization, digital media expansion, shifting aesthetic preferences, weakening intergenerational cultural transmission, and the declining role of customary institutions. Consequently, the philosophical, religious, and ecological meanings of Tumula have gradually diminished. The novelty of this study lies in positioning Tumula as an ecological cultural symbol analyzed through the integrated perspectives of Maqāṣid al-Sharīʿah and Islamic ecotheology, while proposing the RIASED Model (Revitalization through Integration of Adat, Sharīʿah, Ecology, Education, and Digitalization) as an implementable framework for cultural revitalization, environmental stewardship, and the preservation of Gorontalo cultural identity.